Investigating the Impact of Topics’ Selection on Listening Strategy Use for English for Academic Purposes The Case of First Year Students of Master degree at Mohamed Cherif Messadiaa - Amira BOUKARAA (My University, 2023)
Abstract Listening is a very important skill in learning, and selecting topics for this skill is a hard task especially in the high level education. The study aims to investigate the impact of topics ‘selection on listening strategy use for English for academic purposes in the Department of the English Language at Mohamed Cherif Messaadia University, in Souk-Ahras. This exploratory, research utilized a mixed method to collect both quantitative and qualitative data. The main instruments which had been used is a questionnaire comprised of 21 questions was administered to n57 students chosen randomly from N92 Master one EFL Students, Department of English, Souk-Ahras University. The obtained findings unearthed that effective topic selection plays a significant role in enhancing students' engagement, motivation, and comprehension during listening tasks. When topics align with students' interests, knowledge, and language proficiency, they are more likely to actively participate and develop their listening skills. Furthermore, choosing topics relevant to academic contexts helps students acquire the necessary vocabulary and language skills required for success in academic settings. By incorporating a range of academic topics that represent different disciplines, teachers can broaden students' understanding of academic language and consepts. Based on these results, the hypotheses are confirmed. Therefore, Choosing topics that interest the students to stay engaged, motivated and excited to listen will increase their abilities and develop their listening strategy use for English for academic purposes. ------------------ يعد الاستماع مهارة مهمة جدا في التعلم، و يعد اختيار المواضيع لهذه المهارة مهمة صعبة خاصة في التعليم العالي. تهدف الدراسة الى معرفة أثر اختيار المواضيع على استخدام إستراتيجية الاستماع للغة الإنجليزية للاغراض الاكاديمية في قسم اللغة الإنجليزية بجامعة محمد الشريف مساعدية بسوق اهراس. استخدم هذا البحث الاستكشافي طريقة مختلطة لجمع البيانات الكمية والنوعية. الأدوات الرئيسية التي تم استخدامها هي استبيان يتكون من 21 سؤال، تم إعطاؤه ل 57 طالب من قسم ماستر 1 تخصص لغات اجنبية لجامعة محمد الشريف مساعدية تم اختيارهم عشوائيا من بين 92 طالب. كشفت النتائج التي تم الحصول عليها ان الاختيار الفعال و المناسب الموضوع يلعب دورا مهما في تعزيز مشاركة الطلاب و تحفيزهم واستيعابهم أثناء مهام الاستماع. عندما تتوافق المواضيع مع اهتمامات الطلاب ومعارفهم وكفاءتهم اللغوية، فمن المرجح أن يشاركوا بنشاط ويطوروا مهارات الاستماع لديهم. علاوة على ذلك، فإن اختيار المواضيع ذات الصلة بالسياقات الأكاديمية يساعد الطلاب على اكتساب المفردات والمهارات اللغوية اللازمة للنجاح فيها للاغراض الأكاديمية. من خلال دمج مجموعة من المواضيع الأكاديمية التي تمثل تخصصات مختلفة، يمكن للمعلمين توسيع فهم الطلاب للغة والمفاهيم الأكاديمية. وبناءً على هذه النتائج، تم تأكيد الفرضيات. ولذلك، فإن اختيار المواضيع التي تهم الطلاب للبقاء منخرطين ، متحمسين و متشوقين للاستماع سيزيد من قدراتهم ويطور استراتيجية الاستماع لديهم لاستخدام اللغة الإنجليزية للأغراض الأكاديمية. ------------------------- Résumé L'écoute est une compétence très importante dans l'apprentissage, et sélectionner des sujets pour cette compétence est une tâche difficile spécialement dans l'enseignement supérieur. L’étude vise à étudier l’impact des sujets sélection sur l'utilisation de la stratégie d'écoute pour l'anglais à des fins académiques au Département des Langue anglaise à l'Université Mohamed Cherif Messaadia, à Souk-Ahras. Ce exploratoire, la recherche a utilisé une méthode mixte pour collecter des informations à la fois quantitatives et qualitatives, données. Le principal instrument utilisé est un questionnaire composé de 21 questions, a été administré à des étudiants n57 choisis au hasard parmi les étudiants N92 Master one EFL, Département d'anglais, Université Souk-Ahras. Les résultats obtenus ont mis en évidence que une sélection efficace des sujets joue un rôle important dans l'amélioration de l'engagement des étudiants, la motivation et la compréhension lors des tâches d’écoute. Lorsque les sujets correspondent à ceux des éétudiant intérêts, connaissances et maîtrise de la langue, ils sont plus susceptibles de participer activement et développer leurs capacités d'écoute. De plus, choisir des sujets pertinents aux contextes académiques aide les étudiants à acquérir le vocabulaire et les compétences linguistiques nécessaires pour réussir dans milieux académiques. En incorporant une gamme de sujets académiques qui représentent différent disciplines, les enseignants peuvent élargir la compréhension des étudiants du langage et des concepts académiques. Sur la base de ces résultats, les hypothèses sont confirmées. Par conséquent, merci choisir des sujets qui intéressent que les étudiants restent engagés, motivés et enthousiastes à l'écoute augmenteront leurs capacités et développer leur stratégie d’écoute en utilisant l’anglais à des fins académiques.